Genetic and Biochemical Characterization of an Exopolysaccharide With in vitro Antitumoral Activity Produced by Lactobacillus fermentum YL-11 - Wei, Yunlu; Li, Fei; Li, Le; Huang, Linlin; Li, Quanhong (Frontiers in Microbiology, 2019)
In the present study, the whole genome sequence of Lactobacillus fermentum YL-11, a novel exopolysaccharide (EPS)-producing lactic acid bacteria strain isolated from fermented milk, was determined. Genetic information and the synthetic mechanism of the EPS in L. fermentum YL-11 were identified based on bioinformatic analysis of the complete genome. The purified EPS of YL-11 mainly comprised galactose (48.0%), glucose (30.3%), mannose (11.8%), and arabinose (6.0%). In vitro, the EPS from YL-11 exhibited inhibition activity against HT-29 and Caco-2 colon cancer cells, suggesting that EPS from strain YL-11 might be used as an antitumoral agent. EPS at 600 μg/mL and 800 μg/mL achieved inhibition rates of 46.5±3.5% and 45.6±6.1% to HT-29 cells, respectively. The genomic information about L. fermentum YL-11 and the antitumoral activity of YL-11 EPS provide a theoretical foundation for the future application of EPS in the food and pharmaceutical industries.